오존이 기린초와 비비추의 광합성, 항산화효소, 해부학적 구조에 미치는 영향 - 정효정(Hyo-Cheng Cheng); 우수영(Su Young Woo); 이성한(Seong Han Lee); 백생글(Saeng Geul Baek) (Weon'ye gwahag gi'sulji, 2010)
The objective of this study was to identify the effects of ozone on the two species in controlled environment. $Sedum$ $kamtschaticum$ and $Hosta$ $longipes$ were exposed in both control and ozone chamber to investigate photosynthesis, antioxidant enzyme activity, visible damage, the number and the size of stomata and the plastogloubuli. Ozone was fumigated in the concentration of $200μg{·}kg^{-1}$ for 8 hours in a day (from 08:00 AM to 04:00 PM). Firstly, net photosynthesis of two species was decreased after ozone fumigation. Secondly, glutathione reductase activities showed significant difference between control and ozone treatment. Thirdly, visible symptoms of leaves were expressed such as chlorosis, necrosis and decoloration. Also, the size of stoma was significantly decreased in ozone-exposed plants. Furthermore, the intercellular space of $Hosta$ $longipes$ showed increased phenomenon because the mesophyll was collapsed. The number and the size of the plastogloubuli were significantly larger in ozone stress. 이 연구의 도심 녹화 수종으로 가장 많이 이용되는 기린초($Sedum$ $kamtschaticum$)와 비비추($Hosta$ $longipes$)를 대상으로 오존에 의해 나타나는 광합성률, 항산화 효소활성, 해부학적 차이를 구명하기 위하여 수행되었다. 오존을 하루 8시간씩(08:00-16:00) $200μg{·}kg^{-1}$ 처리하였다. 대조구를 설정하고 광합성률, 항산화 효소활성, 해부학적 특성(기공, 플라스토글로블리의 크기 등)을 조사하였다. 그 결과, 오존처리 후 측정된 순광합성량은 두 식물 종에서 감소하였고 호흡률은 증가하였다. 오존처리 후 비비추의 경우 glutathione reductase의 활성이 통계적으로 유의하게 증가하였다. 기린초와 비비추는 황화, 백화 및 반점 등의 전형적인 오존 피해 증상을 나타내었다. 오존 처리후 기린초와 비비추의 단위면적당 기공의 수는 증가하였으며, 기공크기는 유의성 있게 감소하였다. 대기오염에 피해 받은 식물에서 관찰 할 수 있는 플라스토글로블리의 수가 기린초와 비비추에 있어 유의성 있게 증가하고 그 직경도 증가하였다.